The Role of Multimedia Integration in Teaching Islamic Religion and Students' Satisfaction with Interactive Learning in Islamic Boarding Schools in Indonesia - Supriandi, Supriandi; Haddar, Gamar Al; Halim, Chandra (Eastasouth Institute, 2024)
This study investigates the role of multimedia integration in teaching Islamic religion and its impact on student satisfaction with interactive learning in Islamic boarding schools in Indonesia. Using a quantitative research design, data were collected from 160 students through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that multimedia integration significantly enhances the effectiveness of teaching Islamic religion (Path Coefficient = 0.625, p < 0.001), improves student satisfaction (Path Coefficient = 0.664, p < 0.001), and promotes interactive learning (Path Coefficient = 0.686, p < 0.001). Additionally, effective teaching of Islamic religion positively influences interactive learning (Path Coefficient = 0.403, p < 0.001), and higher student satisfaction contributes to more interactive learning experiences (Path Coefficient = 0.234, p = 0.003). The findings emphasize the significance of incorporating multimedia technologies in religious education to provide captivating and efficient learning settings. These findings provide significant knowledge for educators and policymakers who seek to improve the standard of religious teaching in Islamic boarding schools.